2021
DOI: 10.1111/aogs.14214
|View full text |Cite
|
Sign up to set email alerts
|

Factors to consider when seeking better results in placenta accreta spectrum

Abstract: Although it takes time, with effort and dedication this human group becomes a high-performance team. 4Although the term "centers of excellence" has been postulated to describe those hospitals with exceptional characteristics in terms of cases attended volume, resources, and work dynamics. 5 We consider that establishing rigid requirements to "endorse" a hospital for the care of PAS patients may be inappropriate given the diverse realities in multiple countries (availability of resources and specialists, teamwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Inclusion criteria were based on the final preoperative diagnosis following preoperative ultrasound imaging consistent with PAS and on intraoperative confirmation during surgery. 13 , 14 , 15 All pregnant women were selected on the basis of specific preoperative ultrasound imaging and intraoperative staging 13 , 15 , 16 , 17 in our hospital, no woman had massive bleeding immediately before surgery, and all surgery was performed as an elective procedure in our hospital. Antepartum hemorrhage in PAS can occur and cause an emergency situation where preoperative diagnosis cannot be made.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were based on the final preoperative diagnosis following preoperative ultrasound imaging consistent with PAS and on intraoperative confirmation during surgery. 13 , 14 , 15 All pregnant women were selected on the basis of specific preoperative ultrasound imaging and intraoperative staging 13 , 15 , 16 , 17 in our hospital, no woman had massive bleeding immediately before surgery, and all surgery was performed as an elective procedure in our hospital. Antepartum hemorrhage in PAS can occur and cause an emergency situation where preoperative diagnosis cannot be made.…”
Section: Methodsmentioning
confidence: 99%
“…According to the SMFM guidelines, the role of iliac artery occlusion (internal and common arteries) is still controversial as it has been reported to decrease blood loss in some studies but showed no difference in others [2]. It also has been postulated that PAS is associated with neovascularisation and abnormal blood supply therefore occluding pelvic vessels may exacerbate bleeding from the collateral circulation, thus limiting the benefit of this procedure [17][18][19][20][21][22][23][24][25][26]. International Federation of Obstetrics and Gynecology (FIGO) does not recommend its routine use due to a lack of strong supporting evidence of their benefit [1].…”
Section: Discussionmentioning
confidence: 99%
“…Sector S2 is vascularized by deep vessels, which significantly increases surgical complexity and presents an increased risk of hemorrhage [13] . S1/S2 uterine sector classification can provide important information for surgical strategies, especially the use of aortic control during surgery [14 , 15] .…”
Section: Discussionmentioning
confidence: 99%